Factors Affecting Brand Preference of Scooters among Women Consumers in Kathmandu Valley - Malla, Riya (Journal of Business and Social Sciences Research, 2018)
The trend of using scooters nowadays is a key to support consumer daily movement; the increasing number of sales of scooters shows a good sign for vehicle industry. The main objective of the research is to identify and analyze the factors that leads to brand preference of a scooter and which among them led to purchase of scooters. The findings of the study are based on the primary survey of 200 users of different brands, conducted within Kathmandu Valley. Correlation test is applied to test the relationship between the factors and the customer satisfaction. It is found that majority of the respondents considered comfort, mileage and design as the top three important factors that influence brand preference of scooters. The bottom three factors are colour variety, resale value and size of fuel tank. Factors such as price, mileage, comfort level, colour variety, design, size of fuel tank and spare parts supply have significant role in the brand preference of scooters, which means a favorable change in these factor can lead to brand preference of the customers. Whereas, resale value and durability are factors which have no significant relationship with brand preference of scooters among women consumers. From the result obtained, it is recommended that scooter brands should focus in developing more comfortable scooters because research shows that comfort level is the major factor that affects brand preference of scooter. In a city like Kathmandu valley, customers prefer scooter which has higher mileage potential. Although resale value and durability are the least influencing factors still the scooter brands should not neglect these factors because though not so significant but still few customers would prefer such factors while purchasing a scooter. The scooter brands should also focus of providing excellent reach of spare parts supply as majority of the customers agree that they will not purchase a brand of scooter if its spare parts are not easily available. Journal of Business and Social Sciences Research, Vol. 1, No. 2, pp. 185-200